CURRENT AND FUTURE TREND OF RESEARCH IN ACADEMIC WRITING: A BIBLIOMETRIC ANALYSIS - Ambarwati, Evi Karlina; Dewi, Indah Purnama; Utami, Praditya Putri; Puspitaloka, Nina; Nazar, Alvin Yahya Makarim (Journal of English Educational Study (JEES), 2024)
This study was a comprehensive bibliometric analysis of the literature of Academic Writing in various higher education contexts and mapped the current state of the trend as well as identified gap for future research. 991 documents were retrieved on Academic Writing in Higher Education from database citation index Scopus (2013 to 2022) under certain conditions. The documents were then analyzed using OpenRefine version 3.5.2, VOSviewer version 1.6.17 from Leiden University, Microsoft Excel and Tableu Desktop from the perspectives of the number of yearly publications, countries, authors, citation numbers, and keywords. The findings show that the number of publications on Academic Writing is generally growing.The research topics shows that academic writing instruction across classroom contexts reflect the 21st century life skills and learning through students’ active participation, i.e. peer assessment, peer learning, and self-regulation. Likewise, information, media and technology are instilled through e-learning and computer-aided instruction. Last, the functional view of grammar in academic writing establishes new research focus.